The effects of multimedia advertising on building brand equity - Reza Pirayesh; Masoud Ghaempanah (Management Science Letters)
This paper presents an empirical investigation to study the effects of multimedia advertisement on building brand equity. The proposed study uses two questionnaires, one for multimedia advertisement, which consists of 17 questions and the other one for measuring brand equity. The survey is applied among 384 randomly selected customers who do their daily businesses with banks located in province of Kordestan, Iran. Using Pearson correlation as well as linear regression techniques, the study has determined a positive and meaningful relationship between these two variables. In our survey, word of mouth advertisement seems to have the highest impact on brand equity followed by having seminars.